Faktor Predisposisi Penerapan Inisiasi Menyusi Dini - Zakaria, Fatmah (Lembaga Penerbit dan Publikasi Ilmiah (LPPI) Universitas Muhammadiyah Palopo, 2023)
Introduction: In Indonesia, approximately 20 babies die per hour in infants less than one year old and nearly 50% of these infant deaths occur in less the one month. At this time newborns are very vulnerable to morbidity and mortality, especially infectious diseases coused by low body resistance. Purpose: This study analyze predisposing factors with the application of early breastfeeding initiation (IMD) in Gorontalo district. This research was conducted in two puskesmas namely the Tibawa Health Center and Limboto Health Center. Methods: Analitical survey with a cross-sectonal approach. The subjects in this study were all midwives working at the Tibawa Health Center and the Limboto Health Center totaling 36 midwives. Results: This study shows that in the Tibawa Health Center there is a relationship between length of work and the application of IMD p value (0,05), knowledge with the application of IMD p value (0,01) and attitude with the application of IMD p value (0,05). While the rusultfor the Limboto Health Center are that there is a relationship between length of work and the application of IMD p value (0,02), knowledge with the application of IMD p value (0,00) and the attitude with the application of IMD p value (0,01).